The influence of incarceration length and protection status on perceptions of prison social climate - Casey, Sharon (Criminal justice and behavior, 2016)
Using a 2 (incarceration length) ? 2 (custody type) between-groups design, the present study assessed whether inmates? perceptions of the prison social climate were influenced by their security classification and length of time they had been incarcerated. Analyses of data collected from 76 male prisoners who completed a 15-item measure of prison social climate revealed an interaction effect between length of incarceration and protective prisoner status. Those housed in protective custody who had been incarcerated for longer than 6 months rated the social climate significantly more positively than both protective custody prisoners incarcerated for less than 6 months and those not in protective custody. This interaction was strongest on those social climate dimensions relating to therapeutic hold and social cohesion. A univariate effect was also observed whereby protective custody prisoners, irrespective of incarceration length, reported that they experienced the environment as less safe than their mainstream (non-protective custody) counterparts.